Problem of excess attenuation in acoustic measurements of gas bubble concentration in the sea - J. SZCZUCKA (Archives of Acoustics, 2014)
This study is aimed at describing the possible errors in the acoustie estimation of gas buble concentration in the sea made by the assumption of the first order scattering approximation, i.e. by neglecting the interaction between individual bubbles enclosed in the water column. An experimental method of counting the bubbles is sketched, results are presented and two different ways of taking into account the excess attenuation in bubbly medium are used for correcting the bubble number, the results being compared. The problem of bubble swarms in the vicinity of the transmitter is also considered.